Chemical characteristics of the sesquiterpenes and diterpenes from Lauraceae family and their multifaceted health benefits: A review. Issue 12 (December 2022) - Feng, Haowei; Jiang, Yiping; Cao, Huihui; Shu, Yuqi; Yang, Xiaoyu; Zhu, Daoqi; Shao, Meng
Abstract: Lauraceae is a large family with significant economic and medicinal value. Bioactive ingredients from Lauraceae plants have contributed greatly to medicines, food nutrients and fine chemical products. In recent years, quite a few sesquiterpenes and diterpenes with unique structures have been achieved from Lauraceae and their potential benefits are embodied in a wide range of health areas. To our knowledge, there is no review to summarizes these constituents and their biological effects systematically. This current work aims to classify and ascribe the structural types and bioactivities of the identified sesquiterpenes and diterpenes. Herein, a total of 362 sesquiterpenes and 69 diterpenes were comprehensively complied. The various bioactivities could be recognized as cytotoxicity, anti-proliferation and/or anti-apoptosis, anti-inflammation, anti-oxidation, anti-bacterium, etc. This updated data could serve as a catalysis of these sesquiterpenes and diterpenes for the future medical and industrial applications. Abstract : Lauraceae; Sesquiterpenes; Diterpenes; Traditional application; Biological activities.